Evapotranspiration measurement in watermelon (Citrullus lanatus) on the Costa de Hermosillo, Sonora, Mexico. - Román Román, Leonardo; Díaz Valdés, Tomás; López Avendaño, Jesús Enrique; Watts, Christopher; Cruz Bautista, Fidencio; Rodríguez Casas, Julio; Cesar Rodríguez, Julio (REVISTA TERRA LATINOAMERICANA, 2017)
Watermelon (Citrullus lanatus) is a fruit that demands a great amount of water. However, there are no studies that show precise quantities of water used nor are there studies that use techniques, such as covariance of vortices, to measure evapotranspiration (ET) due to the high cost of instrumentation. The aim of this study was to estimate ET in watermelon in an arid region. The experiment was carried out on the coast of Hermosillo, Mexico (29° 00´ north and 111° 14 west) during the months from August to November 2014. The Eddy Covariance technique was used to measure actual ET, and the Penman-Monteith equation was used to determine the reference evapotranspiration (ETo). The experimental plot consisted of a drip irrigation system where 166.1 mm were applied, and rainfall contributed 291.5 mm. The ET was 214.4 mm for the entire crop cycle, while ETo was 498.3 mm. Kc values of 0.15, 0.65 and 0.35 were estimated for early stage, mid- and end of season respectively.